Case report: Giant pituitary neuroendocrine tumor presented along with acute visual loss due to pituitary apoplexy after receiving COVID-19 vaccination - Tanaka, Haku; Nishimura, Fumihiko; Nakase, Kenta; Yokoyama, Shohei; Nakagawa, Ichiro; Yamada, Shuichi; Tamura, Kentaro; Matsuda, Ryosuke; Takeshima, Yasuhiro; Kotsugi, Masashi; Park, Young-Soo; Nakase, Hiroyuki (Frontiers in Surgery, 2023)
Objective A case of giant pituitary neuroendocrine tumor presented along with acute visual loss due to pituitary apoplexy after receiving a COVID-19 vaccination is reported.A 45-year-old man was referred for a giant pituitary tumor with bitemporal hemianopsia. A surgical procedure was planned and then delayed due to the COVID-19 outbreak in Japan, with a Pfizer/BioNTech vaccine administered while awaiting surgery. Three days after the second COVID-19 vaccination the patient noted a progressively worsening headache that caused pituitary apoplexy and then a decrease in vision. Emergency surgery was thus performed.Pituitary apoplexy is a rare and life-threatening complication that may occur after undergoing a COVID-19 vaccination.